Water Consumption in Construction Processes - Gautam, Rakesh Kumar; Dubey, Sushil Kumar (Journal of Progress in Civil Engineering, 2025)
Building construction is a highly resource intensive process, concerning use of materials, land, energy and water. In a building’s entire life cycle, water and energy are considered to be the two major pillars that support human activities in it. While there are many studies on embodied energy and recurring energy consumption in buildings, such database appears scanty in the field of water. Similarly, embodied energy of building. Reducing water consumption and improving water efficiency in buildings is a major step towards sustainable water management. Unless the embodied water content of a building is known or measured, water management is not possible .in this thesis we calculate the exactly use/Requirement of water for the onstruction and compare with actual use of water on site.